Exploring the Influence of YouTube Educational Tutorials in Promoting Quality Education for University Students in Pakistan - Shahzad, Umair; Rizvi, Sayyed Aamir Abbas (ACADEMIA International Journal for Social Sciences, 2025)
The core aim of the study is to provide insights of the ways through which students can obtain equal quality of education through YouTube educational tutorials. For that it becomes necessary to obtain the responses of those academic professionals who use YouTube for posting educational tutorials. For that this research major objective was to explore the perception of professors using YouTube channels regarding the significance of YouTube tutorials on university students for the enhancement of quality of education in Pakistan.The method comprises of the type of research based on source of information for data that is collected is primary research that is original and specific to the objective, research questions and hypothesis. The research design is exploratory research design. The data in this research is qualitative via in-depth interviews. The sample comprises of professors with YouTube channels in Pakistan, concentrating on educational tutorials and related content. Total 12 academic professionals who were selected based on criteria such as content relevance, subscriber count, and engagement with the academic community on YouTube. A semi-structured interview guide/checklist is developed for conducting the in-depth interviews. For the analysis of the data Lumivero NVivo 15 software was used in organizing and analyzing the data, enabling a systematic identification of recurring patterns and insights.The findings indicated the intensity of the indicators, thematic coding matrix, word cloud, themes frequency matrix, correlation between the themes, chi-square, discipline wise one-way analysis of variances, Multivariate analysis of variance between disciplines and four themes were inducted and details are in findings.The results show that there is a possible information seeking mechanism via YouTube educational tutorials, while interactive learning is also a significant view of the academic professionals and professors from whom the interviews were conducted resulting in the improvement in the concepts of the university students and providing them the opportunities of quality education while increasing their learning habits. But being restricted in direct sharing of YouTube tutorials from YouTube this platform is not feasible in functionality and users use other social media platforms to share the tutorials.